IMPLEMENTASI PROGRAM PEMBERDAYAAN MASYARAKAT OLEH PERUSAHAAN PERTAMBANGAN MENURUT PERATURAN PEMERINTAH NOMOR 23 TAHUN 2010 TENTANG PELAKSANAAN KEGIATAN USAHA PERTAMBANGAN MINERAL DAN BATU BARA DI KABUPATEN KUTAI KARTANEGARA - Piter, Joni (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTCommunity Empowerment Program (PPM) is one of the obligations that must be implemented by the company with the Government Regulation Nomo 23 Year 2010 and through the PP Mandatory to implement it Increasing the level of awareness of quality of life, social and environmental harmonization is also affecting the business world, on the role of the company to have social responsibility. This is one of the benefits that can be learned by the company from PPM activities. In this context, Community Empowerment activities become a mandatory menu for companies, beyond the responsibilities outlined by the law. The purpose of this study is to determine the applicability of PPM in accordance with corporate vision and mandated by Government Regulation Nomo 23 of 2010 on the implementation of mineral and coal activities, and to find out what is done by the company in its implementation. Community Empowerment Programs that are part of the business, which means that not only have economic and legal obligations (shareholders or shareholders) but also obligations to other stakeholders that access them even more. - the above obligations. For PT Alamjaya Bara Pratama, attention to the company's social development with local residents, communities and employees is increasingly important. The emergence of social problems that allow the cessation of operations and expenses that will become a financial burden as well as a bad reputation and image. The problems in this study are: How to implement PPM in PT ABP. What is the PPM that has been done by PT ABP? The purpose of this research is to describe the implementation of PPM, knowing the implementation of PPM forms that have been carried out by PT ABP.Â  Keywords: Implementation. Community Empowerment Program (PPM)